Technologies of the future: Security and competition aspects - Rolf Hasse (Intereconomics, 1986)
The SDI technology initiative, which is directed towards military ends, and its civil counterpart Eureka pose a challenge to relations between East and West and within the Western world. Professor Rolf Hasse analyses their implications for security and competition.
Keywords: 330; East-West Trade